2015
DOI: 10.1039/c5sm00108k
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous relaxation dynamics and phase behaviour of a liquid crystal confined in a nanoporous solid

Abstract: We report filling-fraction dependent dielectric spectroscopy measurements on the relaxation dynamics of the rod-like nematogen 7CB condensed in 13 nm silica nanochannels. In the film-condensed regime, a slow interface relaxation dominates the dielectric spectra, whereas from the capillarycondensed state up to complete filling an additional, fast relaxation in the core of the channels is found. The temperature-dependence of the static capacitance, representative of the averaged, collective molecular orientation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 103 publications
1
28
0
Order By: Relevance
“…Therefore, both relaxation processes can be discriminated and the corresponding dipolar relaxation strengths provide then access to local molecular ordering. Employing this distinct dynamical behaviour, we could recently show for 7CB, a prominent member of the rod-like cyanobiphenyl nematogens that the ordering in the core region is reminiscent of the bulk behaviour 47 . It is characterised by an abrupt increase in the nematic ordering in the transition region.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, both relaxation processes can be discriminated and the corresponding dipolar relaxation strengths provide then access to local molecular ordering. Employing this distinct dynamical behaviour, we could recently show for 7CB, a prominent member of the rod-like cyanobiphenyl nematogens that the ordering in the core region is reminiscent of the bulk behaviour 47 . It is characterised by an abrupt increase in the nematic ordering in the transition region.…”
Section: Introductionmentioning
confidence: 97%
“…Dielectric relaxation spectroscopy has proven as particularly suitable to achieve such local information on confined LCs [38][39][40][41][42][43][44][45][46][47] . A number of studies on LCs in porous media evi- Sketch of the capacitor geometry for the dielectric relaxation experiments: Gold electrodes were evaporated onto the mesoporous silica membrane, so that the sample forms a simple parallel circuit both in the regime of monomolecular layer coverage (a) and for the completely filled channels (b).…”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental studies of DLCs confined in cylindrical nanopores have revealed a remarkably complex, sometimes very surprising self-assembly behaviour [24,26,[38][39][40][41][42][43]. Experimental studies on HAT6 in AAO indicate that for planar anchoring, i.e., the molecules lie flat on the hydrophilic pore walls, no long-range intercolumnar hexagonal order is detectable for pore diameters d below 20 nm [44].…”
Section: Introductionmentioning
confidence: 99%
“…Diffraction experiments and Molecular Dynamics simulations on partial fillings [45,68] may allow for complementary structural information on the propagation of the phase boundaries in channel space. This will shed light on the remarkably different pathways found here for freezing and melting of discotics.…”
Section: Discussionmentioning
confidence: 99%